All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 128251 by rs4089 last updated on 05/Jan/21
Answered by mathmax by abdo last updated on 05/Jan/21
letI=∫−∞+∞x2e−x2cosxdx⇒I=∫−∞+∞xe−x2(xcosx)dxbypsrtsu′=xe−x2andv=xcosx⇒I=[−12e−x2xcosx]−∞+∞+12∫−∞+∞e−x2(cosx−xsinx)dx=12∫−∞+∞e−x2cosxdx−12∫−∞+∞xe−x2sinxdx∫−∞+∞e−x2cosxdx=Re(∫−∞+∞e−x2+ixdx)and∫−∞+∞e−x2+ixdx=∫−∞+∞e−(x2−2i2x−14+14)dx=∫−∞+∞e−(x−i2)2−14dx=x−i2=te−14∫−∞+∞e−t2dt=πe−14=∫−∞+∞e−x2cosxdxbyparts∫−∞+∞xe−x2sinxdx=[−12e−x2sinx]−∞+∞+12∫−∞+∞e−x2cosxdx=π2e−14⇒I=π2e−14−π4e−14=π4e−14
Terms of Service
Privacy Policy
Contact: info@tinkutara.com